Enterprise Architecture Planning Using TOGAF-ADM at Scoob Telur Company - Gormantara, Alfredo; Emanuel, Andi Wahju Rahardjo (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2020)
Scoob Telur is a company that operates in the distribution of eggs in the Province of East Java, especially in the capital city of Surabaya. Unfortunately, business processes ranging from sales, expenses and report generation are still not supported by the use of IS / IT and the absence of strategic information systems planning or mature enterprise architecture. Besides, based on the results of observations and interviews, it was found that there is no information system that can manage financial processes systematically and there are no applications that can help the company's business processes. Based on these, an information system and information technology are needed that can be used to manage the financial process and also control and monitor the company so that it can advance the performance and service of the Scoob Telur company. Enterprise architecture design uses TOGAF ADM, which is a detailed framework used to design, evaluate and build architecture enterprise. The results of this research provide a design that determines business architecture, data architecture, application architecture, technology architecture, and opportunities and solutions and also includes application system design proposals so that it can support business processes as well as making reports that occur on Scoob Telur.